2018
DOI: 10.1096/fj.201800227rr
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic astrocyte‐derived neurotrophic factor affords neuroprotection to early brain injury induced by subarachnoid hemorrhage via activating Akt‐dependent prosurvival pathway and defending blood‐brain barrier integrity

Abstract: This study aimed to explore the neuroprotective effect of mesencephalic astrocyte-derived neurotrophic factor (MANF) protein on early brain injury caused by subarachnoid hemorrhage (SAH) and the relevant mechanisms in experimental rats, expecting to understand whether MANF was a potential therapeutic target for SAH treatment. A perforation model of SAH was introduced into the study. Recombinant human MANF (rh-MANF) and protein kinase B (Akt) inhibitor (MK2206) were used to explore the effect and the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…In earlier studies, MANF was shown to be induced at the early stage of brain ischemia, decreasing to the control level at 1 wk after ischemia[ 17 , 46 ]. The protein levels of MANF started to increase at 3 h, and peaked at 24 h in a rat model of intracerebral or subarachnoid hemorrhage[ 47 , 48 ]. These results indicated that MANF was induced by ER stress in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, MANF was shown to be induced at the early stage of brain ischemia, decreasing to the control level at 1 wk after ischemia[ 17 , 46 ]. The protein levels of MANF started to increase at 3 h, and peaked at 24 h in a rat model of intracerebral or subarachnoid hemorrhage[ 47 , 48 ]. These results indicated that MANF was induced by ER stress in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, extracellular MANF was shown to protect human neuroblastoma SH-SY5Y cells from 6-hydroxydopamine (6-OHDA) induced cell death via the activation of PI3K/Akt/mTOR pathway (Hao et al, 2017). In addition to mTOR, several other downstream effectors of the PI3K/Akt signaling pathway including GSK3β, MDM2, and NF-κB have been reported to be activated by treatment of recombinant hMANF in the rodent brain, which was associated with enhanced neuron survival in neurodegenerative diseases and intracerebral hemorrhage models (Hao et al, 2017;Zhang et al, 2017b;Li et al, 2018;Xu M. et al, 2018). MANF has also been reported to activate Erk in a study showing that intracellular MANF overexpression facilitated neuron migration and activated STAT3 and Erk in mice SVZ explant (Tseng et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was conducted as previously described [31]. Proteins from brain samples and cultured BV2 cells were lysed using RIPA lysis buffer.…”
Section: Western Blottingmentioning
confidence: 99%